EMPLOYEE PERFORMANCE EVALUATION BASED ON EXPERTISE INDICATORS, WORK KNOWLEDGE, COORDINATION, NEEDS, DESIRE AND LOYALTY AT THE BHAYANGKARA PRESISI HOSPITAL , GORONTALO REGIONAL POLICE (Journal of Health, Technology and Science (JHTS), 2025)
In this case, Bhayangkara Presisi Hospital, Gorontalo Police is a public service institution that has a great responsibility to ensure that each work unit runs optimally. Therefore, this study aims to identify and evaluate employee performance at Bhayangkara Presisi Hospital, Gorontalo Police through 6 indicators in various work units, such as Medical Records, General Services, Logistics, Planning and Administration (Renmin). This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews . The results of the study indicate that the majority of employees have carried out their duties well according to their educational background, although technical ssstraining is not evenly distributed. Employees show a good understanding of their duties, ability to coordinate, high work motivation, and a professional level of loyalty to their superiors. However, there are still some shortcomings in facilities such as computers and fingerprint devices in several divisions. Performance evaluations are also carried out routinely by superiors through direct observation, and assessments based on documents such as SKP.